(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1900)
Meeting notes for 12 February 1900. Before the meeting began, a brief obituary was read for the Society’s president, the Marquess of Lothian, and Dr James Macdonald both of whom had died since the Jannuary meeting.